The contribution of corporate entrepreneurial dimensions on firm performance in South African non-governmental organisations - Naidoo, Keshan (My University, 2022)
Corporate entrepreneurship (CE) has been suggested by various scholars as occurring when an individual or a group of individuals in an established company display behaviour that is typically practised by individual entrepreneurs. Literature supports the notion that corporate entrepreneurial practices can be implemented as a means to improve company’s performance, and that it may result in an organisation obtaining a competitive advantage. CE dimensions are specific characteristics that are evident in firms that embody the following: innovativeness; risk-taking; proactiveness; autonomy; and competitive aggressiveness. The purpose of this study was to investigate and empirically determine the contribution of CE dimensions on firm performance within South African non-governmental organisations (NGOs) in the health industry, by also considering the moderating effects of the organisation’s climate on this relationship. Furthermore, this study sought to provide important findings that might aid NGOs and other policymakers to determine key interventions that could be included in particular policies, so as to assist such organisations to grow and to remain sustainable, so that they can address the much-needed socio-economic gaps in the South African health sector. A quantitative research technique was used, as the study proposed to measure relationships, as well as predictions, between two or more constructs. A sample size of 103 respondents was aimed for, based on a total target population of 288, with a total of 66 responses having been captured for analysis after the data screening and cleaning process, representing a response rate of 64% from the original targeted 103 sample size. With the exception of the CE dimension of autonomy and proactiveness, the other three dimensions, namely innovativeness, risk-taking and competitiveness were perceived to be key influencers in firm performance in terms of business growth, within South African NGOs that aid in HIV/AIDS research, treatment and care. Interestingly, although the autonomy dimension resulted in a negative influence in its relationship on firm performance, the empirical evidence suggests that, when this dimension is moderated by leadership factors, it changes to a positive outcome on firm performance, thereby confirming that, for positive firm performance to be experienced in South African NGOs, autonomy is a good influencer only if the leadership criteria govern the same. The study further demonstrated that leadership inversely influences the relationship between innovativeness, risk-taking and competitive aggressiveness. In the context of previous literature, such was to have been expected, as it was noted that, for leadership factors to influence relationships in a test positively, the interaction among the particular variables is important, including their moderating and mediating. The interaction terms and the type of leadership factors involved might influence a particular relationship. This study sought to provide empirical evidence suggesting that, by embodying CE in means of its various dimensions, firm performance will be positively influenced in terms of the growth of the business. Such, in turn, should allow such organisations to remain sustainable by means of obtaining a competitive edge, and perhaps even by discovering innovative ways of generating income to drive their socio-economic mission.
A research report submitted in partial fulfilment of the requirements for the degree of Masters of Management (in Entrepreneurship and New Venture Creation) to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2022
Keywords: Innovativeness; Risk-taking; Proactiveness; Compatitive aggressiveness; Non-government organisation; SDG-8: Decent work and economic growth